Avaliação da qualidade em serviços públicos de saúde - o caso da estratégia saúde da família - Righi, Angela Weber (2009)
This study aimed to evaluate the quality of the Family Health Strategy (ESF) through the measurement of users' satisfaction regarding services provided by the program , seeking to identify the link between satisfaction and perceived quality of services by program staff . For this purpose, questionnaires were based on SERVQUAL Scale, which has as a feature comparison between the expectations of the client with regard to provision of service and their perception on it. Thus, this research used the case study method, characterizing it as a descriptive study with cross sectional and quantitative approach. The study was conducted with 606 users of the ESF and 39 professionals from the Health Teams in five units of the ESF in Santa Maria-RS. The data from the application of the SERVQUAL Scale adjusted result showed a negative evaluation of the ESF for both actors: the users show up unhappy and professionals characterized as unacceptable the quality of services. It is important to emphasize that no point was assessed as satisfactory or excellent quality by the actors. However, note that the professionals assigned to all the issues, values higher than those reported by characterizing users, therefore, a slightly better evaluation of officials. This study also identified points of improvement in the environment studied, contributing to the practices currently used by the ESF in the provision of its services are reviewed and reconsidered, using the issues identified here as guiding actions of improvement.